Hot water treatments performed in the base of the broccoli stem reduce postharvest senescence of broccoli (Brassica oleracea L. Var italic) heads stored at 20 °C - Perini, Mauro Alejandro (2017)
Heat treatments cause a moderate and reversible stress that interrupts the normal metabolism (senescence or fruit ripening) of the product. Although there is a large number of reports about heat treatments on broccoli heads, the effect of subjecting only the stems to thermal treatments has not been studied yet. One of the main reasons to analyze this approach is that the hormone ethylene is actively produced in the stem cutting area. Different hot water treatments were performed on the first 5 cm of broccoli stems with various combinations of time-temperature. Treatment carried out at 50 °C for 3 min was chosen for further analysis of different quality and senescence parameters, taking into account that broccoli heads presented a delayed change in Hue and L values when compared with controls during storage. While control heads looked yellow, heat-treated samples retained most of their green colour. Furthermore, control heads presented higher weight loss, lower total and soluble protein, and lower total soluble sugar after 3 or 5 storage days, giving evidence of the fact that a heat treatment just on the stem contributes to the delay of broccoli senescence and to the maintenance of the overall quality of the product during storage.